INITIAL NOTES ON EDUCATIONAL QUALITY: THE IDEB RESULTS AND SOCIOECONOMIC FACTORS - Mello, Liliane Ribeiro de [UNESP]; Bertagna, Regiane Helena [UNESP] (Univ Estadual Paulista-unesp, Fac Ciencias Letras Assis, 2016)
This paper brings a initial discussion about brazilian education quality, obtained through the IDEB - Indice de Desenvolvimento da Educacao Basica (Brazilian Education Development Index). This work was drawn from a qualitative approach together documentary and bibliographic analisys, using IDEB data, illiteracy rate, GDP per capita, GDP and Human Development Index (HDI) of brazilian states. These indicators was shown without pretension of statistical analisys, but urging a thinking/problematization for to understand that the education quality depends on many factors like social and economic conditions of students, which requires effective public policies for improving for everyone.
Keywords: Education quality; Socioeconomic factors; Educational policy